Analisis Sektor Unggulan Perekonomian Kota Banda Aceh - Faisal Faisal (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2014)
This study aims to analyze the dominant sector that has criteria as developed sector and growing rapidly, basic sector, has competitive advantage and specialized in the economy of Banda Aceh city as information and consideration in economic development planning. By using the secondary data in the form of the Gross Regional Domestic Product (GRDP) time series of Banda Aceh city and Aceh Province during the period 2008 to 2012. To reach the purpose, this study it used the Tipology Klassen method, Location Quotient ( LQ ) and shift share analysis that fastilated by Esteban Merquillas. The results of this study indicates that the dominant sector as well as competitive and specialized are electricity and Clean water sector, trade, hotels and restaurants, transport and communication sector, Finance, Real Estate and Services Company with a substantial contribution. The government of Banda Aceh city in an effort to boost the economy with developing dominant sectors that provide high impact for increasing income and employment opportunities in Banda Aceh city area.